Heterogeneous and long-term effects of a changing climate on bird biodiversity - Luoye Chen; Madhu Khanna (Global Environmental Change Advances)
Abstract：: Bird biodiversity in the United States is declining at alarming rates. Despite concerns about the link between climate change and the decline in bird biodiversity, there is limited understanding of the heterogeneous effects of climate change across species and regions and the extent to which these effects persist over time. Using a long-term dataset of the North American bird population from 1980 to 2015, we find statistically significant and robust evidence that an unconditional one-standard-deviation increase in the days above 25 °C (currently 7.8 days in a year but projected to exceed 28 days by the century’s end) decreases bird abundance and species richness by 2.5% and 1.7%, respectively; these effects are more pronounced for specialist birds (4.9% and 2.9%), long-distance migrant specialist species (5.2% and 3.2%), and bird populations in the drier areas, such as the West (7.0% and 2.5%). Additionally, we find no evidence of a diminishing impact of high temperatures on bird biodiversity over this period. Projecting forward to the end of this century, our models suggest that, depending on the extent of warming, the abundance and species richness of specialist birds could decline by 7%-16% and 4%-9%, respectively, relative to current levels. Though less pronounced, a statistically significant decline of 1–3% is also projected for generalist bird populations.